2023
DOI: 10.2478/jaiscr-2023-0015
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Approach to Short-Term Wind Power Prediction Using Deep Neural Networks

Tacjana Niksa-Rynkiewicz,
Piotr Stomma,
Anna Witkowska
et al.

Abstract: In this paper, an intelligent approach to the Short-Term Wind Power Prediction (STWPP) problem is considered, with the use of various types of Deep Neural Networks (DNNs). The impact of the prediction time horizon length on accuracy, and the influence of temperature on prediction effectiveness have been analyzed. Three types of DNNs have been implemented and tested, including: CNN (Convolutional Neural Networks), GRU (Gated Recurrent Unit), and H-MLP (Hierarchical Multilayer Perceptron). The DNN architectures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…AI-based datadriven [31] models include various machine learning (ML) algorithms [32,33], such as support vector machine (SVM), extreme learning machines (ELM), and various traditional artificial neural networks (ANNs) represented by back propagation neural network (BPNN). In many studies [34][35][36], AI-based models have shown better predictive accuracy and robustness in complex nonlinear problems [37]. Li et al [38] successfully achieved accurate wind power prediction using the proposed enhanced crow search algorithm optimization-extreme learning machine model, keeping root mean square error (RMSE) and mean absolute percentage error (MAPE) values below 20% and 4%, respectively, effectively reducing the impact of large-scale wind power integration on the grid.…”
Section: Introductionmentioning
confidence: 99%
“…AI-based datadriven [31] models include various machine learning (ML) algorithms [32,33], such as support vector machine (SVM), extreme learning machines (ELM), and various traditional artificial neural networks (ANNs) represented by back propagation neural network (BPNN). In many studies [34][35][36], AI-based models have shown better predictive accuracy and robustness in complex nonlinear problems [37]. Li et al [38] successfully achieved accurate wind power prediction using the proposed enhanced crow search algorithm optimization-extreme learning machine model, keeping root mean square error (RMSE) and mean absolute percentage error (MAPE) values below 20% and 4%, respectively, effectively reducing the impact of large-scale wind power integration on the grid.…”
Section: Introductionmentioning
confidence: 99%